Disinfection of Fruits with Activated Water - Popova, Prof. Teodora P. (JOURNAL OF ADVANCES IN AGRICULTURE, 2019)
The effect of ionized aqueous solutions (anolytes and catholyte) in the processing of fruits (cherries, morellos, and strawberries) for decontamination has been tested. Freshly prepared analytes and catholyte without the addition of salts were used, as well as stored for 7 months anolytes, prepared with 0.5% NaCl and a combination of 0.5% NaCl and 0.5% Na2CO3. The anolyte prepared with a combination of 0.5% NaCl and 0.5% Na2CO3, as well as the anolyte obtained with 0.5% NaCl, exhibit high antimicrobial activity against the surface microflora of strawberries, cherries, and sour cherries. They inactivate E. coli for 15 minutes. The other species of the fam. Enterobacteriaceae were also affected to the maximum extent, as is the total number of microorganisms, especially in cherries and sour cherries. Even stored for 7 months, they largely retain their antimicrobial properties. Anolyte and catholyte, obtained without the addition of salts, showed a lower effect on the total number of microorganisms, but had a significant effect on Gram-negative bacteria, and especially with regard to the sanitary indicative E. coli.